Spontaneous perirenal and subcapsular haematoma - report of 5 cases - Vukelić-Marković, Mirjana (Radiology and oncology (Ljubljana), 2004)
Background. Spontaneous perirenal and subcapsular haemorrhage is a rare but important clinical condition and is diagnostically very challenging. Sometimes, the aetiology of bleeding remains unclear when all available diagnostic possibilities are exhausted, therapeutic approach still remains controversial. Case reports. We present a series of 5 patients with perirenal and subcapsular bleeding. In two of among our patients, the initial or controlCT scan suggested angiomyolipoma and renal cyst as the cause of the bleeding that was confirmed by pathological analyzes. In other three patients,no pathology other than haematoma itself was visualized on CT scans, nor it was discovered on pathological analyzes in two of the patients. Our CT findings closely correlated with pathologieal findings - whether positive or negative for the pathologieal substrate. Interestingly, we found not one case of renal cell carcinoma. Conclusions. In literature, in as many as 50% of cases of perirenal and subcapsular bleeding, a malignant tumour is found. Therefore, by some authors, nephrectomies in all patients are recommended, butothers take more expectative approach with long-term close surveillance. Webelieve, that with new imaging modalities, if using optimal examination technique and follow-up protocols, tlve patients with bleeding due to benign disease should be recognized and unnecessary nephrectomies avoided.
Keywords: Age Factors; Diagnosis; diagnostika; Hematom; Hematoma; hematomi; Kidney Diseases; krvavitev; Ledvica, bolezni; ledvične bolezni; Sex Factors; Spolni faktorji; Starostni faktorji; Tomografija radiografska, računalniška; Tomography, X-Ray Computed